A case study : using choice experiment in an open distance learning - Tan, Joshua Juat-Huan; Chiam , Chooi Chea (2014)
There are approximately 62 private higher education providers in Malaysia as on May 2014. Among them, there are several institutions offer the open and distance (ODL) mode of teaching and learning pedagogy. Due to the ODL flexibility mode, there has been quite a stir of competition in the education industry. Learners of ODL tend to be more challenging to fulfill their needs as they have other commitments in life, hence the ODL mode to be chosen. Therefore, the ODL education institution need to able to read and provide the necessary needs to these learners. The aim of this study is to investigate the attributes that contributes to choosing an ODL private higher education institution in Malaysia and to explore the consumer behavior in the area of student choice, and consumers’ willingness-to-pay price. Although there are studies on the attributes that influence student choice of a university, but has failed to use the choice experiment theory to examine the attributes that influence choice of course particularly an ODL mode. The sample population was 320 using face-to-face interview. The results would be able to introduce the right marketing strategy for the institution in Malaysia. (Abstract by author)